2006
DOI: 10.1177/016264340602100304
|View full text |Cite
|
Sign up to set email alerts
|

Increased Content Knowledge of Students with Visual Impairments as a Result of Extended Descriptions

Abstract: The National Center for Accessible Media has developed a technology and protocol for inserting extended, enhanced descriptions of visually based concepts into artificially paused digital video. These “eDescriptions” describe material not fully explained by a narrator and provide analogies and explanation specifically designed for students who are visually impaired. In two experiments, fourth-grade students with visual impairments listened to video clips of narrated, age-appropriate curricular material with eDe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…He found that the observable degree of regularity of words in the VD corpus might facilitate the automatic production of VD. Peli [25], Pettit [26], Schmeidler [27] and Ely [28] reported on evaluations done by the VII on the value and importance of VD.…”
Section: The Nature Of Vdmentioning
confidence: 99%
“…He found that the observable degree of regularity of words in the VD corpus might facilitate the automatic production of VD. Peli [25], Pettit [26], Schmeidler [27] and Ely [28] reported on evaluations done by the VII on the value and importance of VD.…”
Section: The Nature Of Vdmentioning
confidence: 99%
“…They have done research on the impact of extended descriptions on visually impaired children's comprehension [2] and have studied effective practices for adults in the descriptions of complex STEM graphics [3].…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, it has addressed description as a solution for access to video images within multimedia for students with visual impairments (Corn & Wall, 2002;DCMP, 2009;Ely et al;Hasselbring & Glaser, 2000; Media Access Group at WGBH, n.d.; Sapp, 2009). Previous research findings have indicated that today's digital curriculum has offered more flexible solutions for assuring students' access (Edyburn, 2010;Hitchcock, 2001;Pisha & Coyne, 2001;Rose, 2000Rose, , 2001Hitchcock, Meyer, Rose & Jackson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggested that these formal, language-specific, descriptions helped young students to better understand concepts and make sense of the visual content within the video that they otherwise might miss. Still, the researchers have recommended that much more research in this area is needed (Sapp, 2009;Ely et. al., 2006).…”
Section: Description and Multimediamentioning
confidence: 99%
See 1 more Smart Citation